2007
DOI: 10.1073/pnas.0609752104
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of antiandrogen activity of nonsteroidal scaffolds of marketed drugs

Abstract: Finding good drug leads de novo from large chemical libraries, real or virtual, is not an easy task. High-throughput screening is often plagued by low hit rates and many leads that are toxic or exhibit poor bioavailability. Exploiting the secondary activity of marketed drugs, on the other hand, may help in generating drug leads that can be optimized for the observed side-effect target, while maintaining acceptable bioavailability and toxicity profiles. Here, we describe an efficient computational methodology t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 53 publications
2
80
0
Order By: Relevance
“…In addition, we have used docking, an approach that has been widely applied elsewhere for virtual discovery of new leads for nuclear hormone receptors (Schapira et al, 2000(Schapira et al, , 2001(Schapira et al, , 2003a as well as many other therapeutic targets (Leach et al, 2006;Bisson et al, 2007;Zhang et al, 2007). We found that some of the antagonists, such as ketoconazole and itraconazole, generally score well; this may be because the docking program picks up nonspecific van der Waals interactions of large molecules on the outer surface of the AF-2 site.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have used docking, an approach that has been widely applied elsewhere for virtual discovery of new leads for nuclear hormone receptors (Schapira et al, 2000(Schapira et al, , 2001(Schapira et al, , 2003a as well as many other therapeutic targets (Leach et al, 2006;Bisson et al, 2007;Zhang et al, 2007). We found that some of the antagonists, such as ketoconazole and itraconazole, generally score well; this may be because the docking program picks up nonspecific van der Waals interactions of large molecules on the outer surface of the AF-2 site.…”
Section: Downloaded Frommentioning
confidence: 99%
“…In contrast to other nuclear receptors, such as the androgen receptor (Bohl et al, 2004;Bisson et al, 2007) and thyroid hormone receptor (Schapira et al, 2003b), the majority of publications on PXR have focused primarily on agonists (e.g., those capable of inducing drug metabolism and transporter expression) with clinical implications for drug-drug interactions (Ung et al, 2007). Conversely, there have been very few attempts to address antagonism at PXR, which could be used to diminish agonist interactions that are unavoidable with some treatments, such as with anticancer therapies and macrolide antibiotics such as rifampicin (Mani et al, 2005).…”
mentioning
confidence: 99%
“…To understand the side effects and toxicity of rejected drugs, it is important to predict "OffTarget" binding sites. A number of methods have used clustering of proteins into families [98,99], global structure similarity measurement [100,101] and interface similarity measurement [102][103][104][105] to predict "Off-Target" binding or to redesign drugs to enhance efficacy. Lounkine et al have used a similarity ensemble approach to predict off-targets, based on whether a molecule will bind to a target with similar chemical features to those of known targets [106].…”
Section: Ppi Network and Drug Designmentioning
confidence: 99%
“…A virtual screening protocol identified ER specific ligands from a plant product-based database [32]; from 12 candidates evaluated by a fluorescence polarization binding assay, 3 had >100-fold selectivity to ER over ER . The same approach has also been used to find compounds with good selectivity for ER over ER [32,33]. Bisson et al have used computational methods that led to a nonsteroidal antiandrogen with improved AR antagonistic activity based on an initial screening of FDA approved new drugs [33].…”
Section: Introductionmentioning
confidence: 99%
“…The same approach has also been used to find compounds with good selectivity for ER over ER [32,33]. Bisson et al have used computational methods that led to a nonsteroidal antiandrogen with improved AR antagonistic activity based on an initial screening of FDA approved new drugs [33]. Several groups have published datasets or performed modeling on ER and AR and these data are readily available for further evaluation with new modeling methods [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%